EFFECT OF PROPRANOLOL ON PROLACTIN IN ADULT MALE RATS: Effect of Propranolol on Prolactine - Naveed, Abdul Khaliq; Ali, Liaqat; Minhas, Liaqat Ali; Tahir, Muhammad (Pakistan Armed Forces Medical Journal, 2008)
Objectives: The study was aimed to observe the effect on blood serum level of prolactin in propranolol treated adult male rats.Design: A experimental study.Place and Duration of Study: The study was done at Army Medical College Rawalpindi, National Institute of Health Sciences and NORI, Islamabad from Jan to Aug 2005.Materials and Methods: Adult male rats were used in the study. Rats were divided into four groups A (Control) and B, C and D (Treatment) each containing fourteen rats. Propranolol 1 mg, 2 mg and 4 mg/kg body weight intraperitoneally daily for sixty days was given to treated groups respectively and control group with 0.5 ml of distilled water. The blood serum level of prolactin was measured in half of the rats of all groups by Enzyme Immunoassay Method. Half of the rats were left for recovery to take place for another sixty days. The above procedure was adopted for the measurement of the prolactin level in the recovered rats. One way ANOVA was used to analyze the data. Results: The prolactin level in control and treated groups rat were 4.75 ± 1.4 ng/ml serum, 4.70 ± 1.1 ng/ml serum, 4.51 ± 1.7 ng/ml serum and 3.1 ± 0.8 ng/ml serum respectively. Prolactin level was significantly low (p < 0.05) in 4 mg treated groups when compared with control, treated 1 mg and 2 mg groups. After recovery period of sixty days insignificant difference in prolactin level between control and recovered groups was observed.Conclusion: Pattern of low prolactin level was observed following propranolol treatment in male rats.